Decay rate of the solutions to the Bresse-Cattaneo system with distributed delay - Choucha, Abdelbaki; Alharbi, Asma; Cherif, Bahri; Jan, Rashid; Boulaaras, Salah (AIMS mathematics, 2023)
This study examines the pace at which solutions to a Bresse system in combination with the Cattaneo law of heat conduction and the dispersed delay term degradation. We establish our major finding utilizing the energy approach in the Fourier space.